2019
DOI: 10.1108/ilt-05-2018-0204
|View full text |Cite
|
Sign up to set email alerts
|

Influence of recess shape on comprehensive lubrication performance of high speed and heavy load hydrostatic thrust bearing

Abstract: Purpose This paper aims to describe a theoretical and experimental research concerning influence of recess shape on comprehensive lubrication performance of high speed and heavy load hydrostatic thrust bearing with a constant flow. Design/methodology/approach The lubrication performance of a hydrostatic thrust bearing with different recess shape under the working conditions of high speed and heavy load has been simulated by using computational fluid dynamics and finite volume method. Findings It is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Several theoretical and experimental studies have been published in the open literature related to the thrust pad bearings. [1][2][3][4][5][6][7][8][9] Osman et al 1 scrutinized the experimental study of hydrostatic thrust pad bearing and computed the performance parameters of bearing in terms of fluid film thickness, pressure distribution, and oil flow rate. Further, it was reported that pocket size and shape have a significant influence on the behavior of hydrostatic thrust bearings.…”
Section: Hybrid/hydrostatic Thrust Pad Bearingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several theoretical and experimental studies have been published in the open literature related to the thrust pad bearings. [1][2][3][4][5][6][7][8][9] Osman et al 1 scrutinized the experimental study of hydrostatic thrust pad bearing and computed the performance parameters of bearing in terms of fluid film thickness, pressure distribution, and oil flow rate. Further, it was reported that pocket size and shape have a significant influence on the behavior of hydrostatic thrust bearings.…”
Section: Hybrid/hydrostatic Thrust Pad Bearingsmentioning
confidence: 99%
“…Furthermore, they also proposed that a thin metal plate acts as a fluid restrictor and improves the dynamic stiffness coefficient of bearing. Yu et al [3][4][5] studied the pressure distribution of hydrostatic thrust pad bearing for different pocket shapes (sector, rectangular, elliptical, and I-shaped pockets) using CFD (Computational fluid dynamic) and Finite Volume technique. They revealed that rectangular-shaped recess provides a larger pocket pressure value as compared to other geometric shapes of pocket.…”
Section: Hybrid/hydrostatic Thrust Pad Bearingsmentioning
confidence: 99%
“…A series of studies have been undertaken on active hybrid bearings, in which the part one describes the mathematical model and second part outlines the control design techniques for improving dynamic characteristics [6,7]. The performance characteristics of the hydrostatic bearings are checked against different shapes of recess [8,9] but there is a performance limitation due to the fixed throttling effect. A prototype is developed for the active bearing where the clearance gap is controlled through high-speed solenoid valves but deficiency arises because it is used for light load applications [10].…”
Section: Introductionmentioning
confidence: 99%
“…An active thrust bearing is proposed in Mizumoto et al (1996), where two actuators work in a region around bearing plate, changing plate iconicity results in fluid force. The shape of throttling devices whether throttle is restrictor, recess, servo valve has influence on the static and dynamic characteristics (Shao et al, 2018;Yu et al, 2019;Rehman et al, 2019a). To maintain fluid film thickness, a numerical/experimental approaches have been used to study different mechanism for pressure regulation (Lewis, 1984).…”
Section: Introductionmentioning
confidence: 99%